Proyecto para la creación de un centro de entretenimiento familiar tipo bolocentro en la ciudad de San Franciscoo de Milagro - Bazurto Sellán, Denisse Elizabeth (2010)
This project tries to determine how the idea of the implementation of a entertainment center, bowling style, would develop in Milagro city. Through a marketing study, the potential demand will be determined, such as the likes and entertainment preferences of the potential clients, so the service of the center may be oriented to those features, as well as the localization issue. The technical study helps to determine specific important areas of the center, any need of human or physical resource. In the other hand, the financial study will set the income, cost, working capital, and the convenience and the 10-years- long-term future decisions made for the center will be made in terms of rates. The result of the project will be the identification of the possibility to get the center through, the return rate that it will generate in order to invest and the analysis of the risk. The objective of the project is that the people can spend a nice time with family and friends in a bowling style center.